Short Communication: Diversity and distribution of figs (Ficus spp.) across altitudes in Gunung Tilu, Kuningan, West Java, Indonesia - YAYAN HENDRAYANA; PUDJI WIDODO; CECEP KUSMANA; IMAM WIDHIONO (Society for Indonesian Biodiversity, 2019)
Abstract. Hendrayana Y, Widodo P, Kusmana C, Widhiono I. 2019. Short Communication: Diversity and distribution of figs (Ficus spp.) across altitudes in Gunung Tilu, Kuningan, West Java, Indonesia. Biodiversitas 20: 1568-1574. The genus of Ficus is significant component in tropical rainforest ecosystem, consisting of large number of species and spreading across altitudes. This research was aimed to examine the diversity and distribution of species belong to Ficus genus in Gunung Tilu, Kuningan District, West Java as a basis for building conservation strategies. There were 12 species of Ficus found from the altitudes of 600 to 1000 m asl. The highest number of species was found at the altitudes of 600 - 700 m above sea level with 10 species, while the lowest number of species were found at the altitudes above 1000 m asl with only two species. The highest individual density was found at an altitude of 600 m asl, while the lowest density was at the altitude of 1000 m asl. The distribution pattern of Ficus spreads throughout the region of Gunung Tilu, Kuningan.